2011
DOI: 10.2528/pierb11011205
|View full text |Cite
|
Sign up to set email alerts
|

2.45 GHz (CW) MICROWAVE IRRADIATION ALTERS CIRCADIAN ORGANIZATION, SPATIAL MEMORY, DNA STRUCTURE IN THE BRAIN CELLS AND BLOOD CELL COUNTS OF MALE MICE, MUS MUSCULUS

Abstract: Abstract-Present study examines biological effects of 2.45 GHz microwave radiation in Parkes strain mice. Forty-day-old mice were exposed to CW (continuous wave) microwave radiation (2 h/day for 30 days). Locomotor activity was recorded on running wheel for 12 days prior to microwave exposure (pre-exposure), 7 days during the first week of exposure (short-term exposure) and another 7-day spell during the last week of the 30-day exposure period (long-term exposure). Morris water maze test was performed from 17t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The works of Mcree [30] and Roberts et al [31] reported that several hematological parameters are sensitive to RF/MW exposure, not only in animals, but also in humans. A study conducted by [32] where mice were exposed to 2.45 GHz CW microwave frequency at 2 hrs/day for 30 days reported alteration in blood pictures among others.…”
Section: Mchc For Exposed and Sham Exposed Groupsmentioning
confidence: 99%
“…The works of Mcree [30] and Roberts et al [31] reported that several hematological parameters are sensitive to RF/MW exposure, not only in animals, but also in humans. A study conducted by [32] where mice were exposed to 2.45 GHz CW microwave frequency at 2 hrs/day for 30 days reported alteration in blood pictures among others.…”
Section: Mchc For Exposed and Sham Exposed Groupsmentioning
confidence: 99%
“…range of SAR is 2.0W/Kg [19]. Now-a-days the most popular 3G network system works under the frequency range of 2100 MHz [20]. Mobile phones radiate an average of power of 0.2-0.6 Watt/ Kg, 40% of which is absorbed in the head and neck region [11].…”
Section: Scoring Of Micronucleimentioning
confidence: 99%
“…The diagnostic values of MRI are greatly magnified by the automated and accurate classification of the MRI images [6][7][8].…”
Section: Introductionmentioning
confidence: 99%